Research into the dynamic behaviour of saturated and unsaturated sands, with special reference to the liquefaction and post liquefaction phases - Schlebush, T. B.(Thomas Brummer) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1994.